Selective prebiotic conversion of pyrimidine and purine anhydronucleosides into Watson-Crick base-pairing arabino-furanosyl nucleosides in water - Roberts, Samuel J; Szabla, Rafał; Todd, Zoe R; Stairs, Shaun; Bučar, Dejan-Krešimir; Šponer, Jiří; Sasselov, Dimitar D; Powner, Matthew W (Nature communications, 2018)
Prebiotic nucleotide synthesis is crucial to understanding the origins of life on Earth. There are numerous candidates for life's first nucleic acid, however, currently no prebiotic method to selectively and concurrently synthesise the canonical Watson-Crick base-pairing pyrimidine (C, U) and purine (A, G) nucleosides exists for any genetic polymer. Here, we demonstrate the divergent prebiotic synthesis of arabinonucleic acid (ANA) nucleosides. The complete set of canonical nucleosides is delivered from one reaction sequence, with regiospecific glycosidation and complete furanosyl selectivity. We observe photochemical 8-mercaptopurine reduction is efficient for the canonical purines (A, G), but not the non-canonical purine inosine (I). Our results demonstrate that synthesis of ANA may have been facile under conditions that comply with plausible geochemical environments on early Earth and, given that ANA is capable of encoding RNA/DNA compatible information and evolving to yield catalytic ANA-zymes, ANA may have played a critical role during the origins of life.
Keywords: Mercaptopurine; fotochemické procesy; oxidace-redukce; Origin of Life; merkaptopurin; původ života; Arabinonucleosides; Oxidation-Reduction; Photochemical Processes; arabinonukleosidy